The Role of Lecturers in Fostering a Disciplined Character in Civic Education Students through Problem-Based Learning - Regita Apriliana Cahyani; Andreas Andrie Djatmiko; Winarsih (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study aims to examine the role of lecturers in enhancing the discipline of sixth-semester A Civic Education students through Problem-Based Learning (PBL) and to identify the factors that facilitate or hinder its implementation. The methodological framework employed in this study is characterised by a descriptive qualitative approach, combining techniques such as interviews, observational studies and the analysis of relevant documentation. The findings indicate that lecturers fulfil their roles as role models, facilitators, mentors and motivators, consistently enforcing educational regulations that lead to improved student discipline regarding attendance, assignment submission and collaboration in group work. Contributing factors include educational motivation, collaborative efforts amongst colleagues, and faculty expertise, whilst constraints include time-related constraints, variations in student ability, and low levels of participation amongst certain students. The implementation of PBL is effective in fostering a disciplined character amongst students.